Nigeria’s Foreign Policy in the Shadow of Naira Devaluation: Insights from the President Bola Ahmed Tinubu’s led Administration - Abdullahi, Gali; Lawal , Ahmed; Mohammed, Munir Abubakar (Kashere Journal of Politics and International Relations, 2025)
This paper critically examines the impact of Nigeria's recent naira devaluation, undertaken under President Bola Ahmed Tinubu’s administration, on the nation’s foreign policy. The devaluation policy, intended to unify exchange rates and attract foreign investment, represents a significant shift in Nigeria’s economic trajectory. However, the sharp depreciation of the naira—from approximately ₦460 to over ₦1,700 per US dollar—has triggered widespread economic consequences, including inflation, a rising cost of living, and a substantial increase in Nigeria’s external debt burden in local currency terms. Drawing on dependency theory, the study situates the devaluation within a broader global economic framework, arguing that such policies often reinforce structural dependencies that constrain the economic sovereignty and foreign policy autonomy of peripheral states like Nigeria. The analysis examines how this economic shift has affected Nigeria’s ability to fulfill its constitutional foreign policy objectives and interrogates its implications for Nigeria’s enduring commitments to non-alignment and African unity. The paper finds that while the devaluation may enhance export competitiveness and attract foreign capital, it simultaneously undermines Nigeria’s continental leadership, weakens its diplomatic leverage, and complicates its ability to meet international obligations. It therefore concludes that without comprehensive economic reforms and adequate social cushioning, the current devaluation threatens to erode Nigeria’s foreign policy aspirations. Aligning domestic economic strategies with foreign policy goals is thus imperative to restore Nigeria’s regional influence and sustain its relevance in the global political economy.